2015
DOI: 10.1371/journal.pone.0117489
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphisms of Renin-Angiotensin-Aldosterone System Gene in Chinese Han Patients with Nonfamilial Atrial Fibrillation

Abstract: BackgroundAtrial fibrillation(AF) is the most common arrhythmia in the adult population. The activated renin-angiotensin-aldosterone system (RAS) has been reported to play an important role in the pathogenesis of atrial fibrillation. The aim of this study was to investigate the association between nonfamilial AF and polymorphisms in RAS gene.MethodsA total of 931 patients with nonfamilial AF, 663 non-AF heart disease patients and 727 healthy subjects were selected. 10 tagSNPs (tSNPs) (ACE gene rs8066114, AGT g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
(24 reference statements)
0
8
0
2
Order By: Relevance
“…We speculate that the CGC/CGC diplotype may cause the target cells within the CNS to have impaired transport of its substrates, including endogenous opioid peptide β‐endorphin, from its site of action in the brain into the blood. β‐Endorphin is well known to be involved in the modulation of pain transmission, and it produces analgesia by inhibiting the firing of peripheral somatosensory fibers . As a result of increased β‐endorphin levels in the brain, a better response to experimental cold pain stimuli is therefore observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that the CGC/CGC diplotype may cause the target cells within the CNS to have impaired transport of its substrates, including endogenous opioid peptide β‐endorphin, from its site of action in the brain into the blood. β‐Endorphin is well known to be involved in the modulation of pain transmission, and it produces analgesia by inhibiting the firing of peripheral somatosensory fibers . As a result of increased β‐endorphin levels in the brain, a better response to experimental cold pain stimuli is therefore observed.…”
Section: Discussionmentioning
confidence: 99%
“…b-Endorphin is well known to be involved in the modulation of pain transmission, and it produces analgesia by inhibiting the firing of peripheral somatosensory fibers. 63 As a result of increased bendorphin levels in the brain, a better response to experimental cold pain stimuli is therefore observed. Thus, CGC/CGC diplotype for the c.1236C>T, c.2677G>T/A, and c.3435C>T polymorphisms may predict a lower sensitivity to cold pain stimuli as evidenced by a significantly higher cold pain threshold and cold pain tolerance than those without the diplotype.…”
Section: Discussionmentioning
confidence: 99%
“…GATA and PITX2 genes affect the development of the pulmonary venous myocardium which is involved in the initiation of AF ( Table 1). Several studies reported an increased risk of AF with polymorphism of RAAS system genes encoding angiotensin converting enzyme inhibitor, angiotensin gene promotor, and angiotensinogen (24,65).…”
Section: Non-ion Channel Variantsmentioning
confidence: 99%
“…Ренин-ангиотензиновая система играет важную роль в патогенезе ФП [41], в частности, имеются исследования о роли генов ACE, AGT и AGTR1 в формировании предрасположенности к развитию данной патологии. Молекулярно-генетические маркеры фибрилляции предсердий ации замен M235T, G-6A и G-217A в гене AGT с риском развития ФП [42]; позднее данный факт был подтвержден -аллель T и генотип T/T полиморфизма M235T, а также аллель G и генотип G/G полиморфизма G-6A продемонстрировали ассоциации с повышенным риском развития данной патологии [43,44]. В продолжение, в 2008 г., ýта же группа провела повторное исследование с привлечением большего количества пациентов (1 236 человек).…”
Section: гены ренин-ангиотензиновой системыunclassified